Society, Dispersed Knowledge and Uncertainty Toward Ethical Tales - Zonik, Przemysław; Zonik, Joanna (Wydział Filozoficzny, Uniwersytet im. Adama Mickiewicza w Poznaniu, 2020)
In this article the assumptions of one of the versions of the common good concept in terms of the dispersion of knowledge and uncertainty are analyzed. The article also aims at showing the consequences in regard to moral attitudes in politics and economics which are drawn on the basis of the concepts of this type. In the first part I expound the ontological assumptions which are the basis for the analysis. In the second part the concept of common good in terms of its own assumptions and in relation to the ontology developed in this article is discussed. In the third part I consider some general thoughts about the structure of the ethical tales and their reference.
Keywords: cybernetics; theory of mechanism; dispersed knowledge; uncertainty; politics; common good; ethical claims and reality; ethical tales